Is the Hair Follicle Necessary for Normal Wound Healing? - Ito, Mayumi (2008)
The hair follicle contributes cells to the interfollicular epidermis after wounding, but the functional role of these cells has not been resolved. To address this question, Langton et al. (this issue, 2008) take advantage of the Edaradd mutant mouse, which lacks hair follicles on its tail. They discover an initial sluggish response of the hairless tail epidermis to wounding that is rapidly compensated for by recruitment of epidermal cells from outside the normally responsive area. This suggests that the hair follicle is important but not necessary for normal wound healing.